2011
DOI: 10.1007/s11095-011-0503-9
|View full text |Cite
|
Sign up to set email alerts
|

Disulfide Scrambling in IgG2 Monoclonal Antibodies: Insights from Molecular Dynamics Simulations

Abstract: Consistent with experimental studies, our simulations indicate inter-chain disulfide linkages in human IgG2 mAbs are degenerate. Potential rational design strategies to devise hinge stabilized human IgG2 mAbs are gleaned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
32
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 33 publications
7
32
0
Order By: Relevance
“…17 Molecular dynamic simulation study revealed that the sulfur atoms of inter-chain disulfide bonds are highly mobile and can be in close proximity. 18 Therefore, it is not a surprise to observe the coexistence of multiple disulfide bond isoforms for IgG 2 antibodies. In addition to isoforms from different intramolecule disulfide bond linkages, disulfide bond linked IgG 2 dimer was also found in recombinant IgG 2 from cell culture and in human serum.…”
Section: Free Sulfhydrylsmentioning
confidence: 99%
“…17 Molecular dynamic simulation study revealed that the sulfur atoms of inter-chain disulfide bonds are highly mobile and can be in close proximity. 18 Therefore, it is not a surprise to observe the coexistence of multiple disulfide bond isoforms for IgG 2 antibodies. In addition to isoforms from different intramolecule disulfide bond linkages, disulfide bond linked IgG 2 dimer was also found in recombinant IgG 2 from cell culture and in human serum.…”
Section: Free Sulfhydrylsmentioning
confidence: 99%
“…Although the isoforms only differ in the arrangement of the inter-chain disulfide bonds, each disulfide pattern alters the higher-order structure of the mAb, thereby affecting thermal stability, binding efficiency, surface hydrophobicity, isoelectric point, and possibly influencing developability. 1519 For example, A-isoform enriched panitumumab and denosumab demonstrated higher apparent affinity to the human IgG Fc receptor-like 5 (FCRL5) compared to the B isoform. 20 Disulfide isoform distribution may also affect the conjugation profile of cysteine-linked antibody-drug conjugates.…”
Section: Introductionmentioning
confidence: 99%
“…17,20,2226 The flexible and solvent-accessible hinge region is particularly crucial, as it tends to be labile to reduction and oxidation that can lead to disulfide scrambling or trisulfide formation. 15,17,19,2730 Several mass spectrometry (MS)/MS approaches for characterizing disulfide linkages have been described using collision-induced dissociation (CID), electron-transfer dissociation (ETD), or electron-capture dissociation (ECD). 1113,29,3135 These approaches often require multiple analysis, comparison of reduced and non-reduced peptide maps, interpretation of complex data sets, or large sample consumption.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, computer simulation has become an indispensable tool to study the shape, size, conformational stability, hydrodynamic behavior, folding patterns, and denaturation of such peptides. [24][25][26] So far, about 500 different types of cone snail species are reported. The pioneering work of characterization of cone snail venoms was done by Spence et al 27 They studied the venom from Conus geographus, purified it and attempted to determine its amino acid composition.…”
Section: Introductionmentioning
confidence: 99%
“…Though coarse in nature, this methodology has been used before by computation chemists to characterize the higher order structures in proteins and other biomolecules with reasonable accuracy. 12,26 In D, both the native disulfide bonds are broken and so the reasonably labile peptide is free to explore the energy landscape by acquiring different conformations. Figure 7 shows the distribution of the distances for the three possible combinations of the four cysteine residues to form the two disulfide bonds.…”
mentioning
confidence: 99%